Low-alloy ultrahigh-hardness steel and preparation method thereof
By reasonably designing the chemical composition and heat treatment process of low alloy steel, an ultrafine ultrahard micro-nano structure consisting of nano-scale bainite, nanotwin martensite, residual austenite and possible cementite were prepared, which solved the problems of high element content of existing ultra-high hardness steel alloys and complex preparation processes, and achieved significant improvement in hardness and simplification of the process.
Patent Information
- Application Number
- CN202411867857.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing ultra-high hardness steel has high alloy elements and complex preparation processes, resulting in high production costs and limited application.
By rationally designing the chemical composition and heat treatment process of low alloy steel, ultrafine ultrahard micro-nano structures consisting of nanoscale bainite, nanotwin martensite, residual austenite and possible cementite were prepared.
Under the condition of lower alloy element content, the hardness of low alloy ultra-high hardness steel is significantly improved, and the hardness can reach 63~68 HRC. At the same time, the preparation process is simplified and production costs are reduced.
Smart Images

Figure CN119640147A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of iron and steel metallurgy, and specifically relates to a low-alloy ultra-high hardness steel and a preparation method thereof. Background Art
[0002] Structural parts such as bearings, gears and wear-resistant liners are widely used in modern manufacturing industries, especially in service environments that require high hardness and high wear resistance, which requires the steel materials used to manufacture the above structural parts to have ultra-high hardness. Ultra-hard steel materials usually achieve their ultra-hard properties through special heat treatment and alloying processes. Therefore, in response to this demand, it is extremely important to study the relationship between the composition, heat treatment process, structure and hardness of ultra-high hardness steel.
[0003] Many R&D units have improved and developed the composition and process of ultra-high hardness steel, which are introduced as follows:
[0004] The Chinese patent document with publication number CN111485181B proposes a 700HBW grade ultra-high hardness protective steel plate, the mass percentage of chemical elements of which are: C: 0.65-0.85%, Si: 0.70-1.00%, Mn: 0.40-0.9%, Cr: 0.85-1.35%, Ni: 2-4%, Nb: 0.02-0.07%, Ti: 0.01-0.03%, V: 0.02-0.06%, Mo: 0.20-0.50%, the balance is Fe and other inevitable impurities. The invention obtains a full martensitic structure of primary air-cooled martensite and secondary deep-cooled martensite through rolling + ultra-deep cryogenic treatment process, and the steel plate can have a Brinell hardness value of more than 700HBW at room temperature.
[0005] The Chinese patent document with publication number CN10698900B proposes a production process for low-alloy ultra-high hardness wear-resistant steel plates, whose chemical elements are as follows: C: 0.20-0.25%, Si: 0.30-2.0%, Mn: 1.5-1.9%, Cr: 0.7-1.4%, B: 0.002-0.005%, Ni≤0.50%, Mo≤0.40%, Nb≤0.10%, V≤0.07%, Ti≤0.040%, the total amount of alloy elements is less than 6%, and the rest is Fe and unavoidable impurities. The invention uses the process route of strengthening controlled cooling and offline heating and quenching of the rolled steel plate to produce a wear-resistant steel plate with a hardness greater than 500HB.
[0006] The Chinese patent document with publication number CN109023100A proposes a steel plate with high hardness and ultra-high wear resistance and its production method, the chemical elements of which are as follows: C: 0.33-0.35%, Si: 0.25-0.40%, Mn: 0.50-0.60%, P≤0.010%, S≤0.003%, Cr: 1.10-1.20%, Mo: 0.30-0.35%, Ni: 0.30-0.35%, A1: 0.020-0.040%, Nb: 0.020-0.040%, the balance is Fe and unavoidable impurities. The production method described in the invention includes smelting, continuous casting, heating, rolling, cooling after rolling and heat treatment processes, and the hardness of the produced steel plate is 530-570HB.
[0007] The Chinese patent document with publication number CN107460405A proposes an ultra-high hardness and ultra-high strength special steel and its production method, in which the chemical elements include C, Si, Mn, Fe, and also contain two or more alloy elements of Cu, Al, Ni, Nb, W, Bi, Ti, V, RE (rare earth), Cr, Ca, Mg, Mo, Sb, B, Zn, and Zr, and the total content of alloy elements exceeds 6%. The invention uses annealing + quenching + tempering process to obtain a hardness range of 60 to 68HRC for the ultra-high hardness and ultra-high strength special steel.
[0008] The ultra-high hardness steels involved in the above invention patents all have high element content and complex preparation processes, but the high cost of raw materials and complex processes will limit the application of the corresponding ultra-high hardness steels in the manufacturing industry. Based on this background, it is urgent to develop an ultra-high hardness steel with low alloy and simple production process to meet the needs of specific industrial applications. Summary of the invention
[0009] The purpose of the present invention is to provide a low alloy ultra-high hardness steel and a preparation method thereof. Through material innovation and process improvement, low alloy ultra-high hardness steel is prepared, which has extremely high social and economic benefits.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] One of the technical solutions of the present invention is to provide a low-alloy ultra-high hardness steel, the raw material of which is low-alloy steel; the matrix structure of which is composed of nano-scale bainite, nano-twinned martensite lamellae and residual austenite, or is composed of nano-scale bainite, nano-twinned martensite lamellae, residual austenite and cementite;
[0012] The raw material of the low alloy ultra-high hardness steel is low alloy steel. The chemical composition of the low alloy steel, in addition to iron, includes, by mass percentage, C 0.8%-1.0%, Si 1.2%-1.8%, Al 0.05%-0.5%, Cr 1.0%-1.8%, Mo 0-0.6% and inevitable impurities, wherein the mass percentage ratio of C, Si, Al, Cr and Mo meets 0≤δ≤0.83, δ=[Cr 1 / 3 -(Si-C)]×[(0.25×Mo+Al)] 1 / 2 .
[0013] Based on the element cost and clear understanding of the role of each alloying element and the content control principle, the present invention rationally designs the alloy components of low-alloy ultra-high hardness steel: C, Si, Cr, Al and Mo. On the basis of rationally controlling the chemical composition range of each element, the relationship is adjusted by regulating the formula: 0≤δ≤0.83, δ=[Cr 1 / 3 -(Si-C)]×[(0.25×Mo+Al)] 1 / 2 , regulate the ratio of C, Si, Cr, Al and Mo alloying elements, clarify the relative addition amount of some key elements, so that the relevant elements play a key role in regulating the ultra-high hardness of the steel of the present invention. The δ value is controlled between 0 and 0.83. Too high a δ value will lead to high alloy cost of ultra-high hardness steel, complicated preparation process and component segregation, and too low a δ value will reduce the hardness value, making it difficult to achieve the corresponding reasonable value of the prepared organization ratio, and even deteriorate the comprehensive mechanical properties.
[0014] Preferably, the lath size of bainitic ferrite in the nano-scale bainite is 30-120 nm; and the thickness of the nano-twinned martensite lamellae is 5-15 nm.
[0015] Bainitic ferrite is a substructure of bainite.
[0016] Preferably, the content of the nano-scale bainite is 20-70%, the content of the retained austenite is 15-20%, and the content of the cementite is 0-10%.
[0017] Preferably, the hardness of the low alloy ultra-high hardness steel is 63-68HRC.
[0018] The second technical solution of the present invention is to provide a method for preparing the above-mentioned low-alloy ultra-high hardness steel, comprising the following steps:
[0019] The low alloy steel is subjected to austenitization treatment, then cooled to Ms-10 to Ms+50°C at a first cooling rate, kept warm, then cooled to 25±2°C (room temperature) at a second cooling rate, and finally subjected to tempering stabilization treatment to obtain a low alloy ultra-high hardness steel;
[0020] The range of the first cooling rate is >5°C / s;
[0021] The second cooling rate is in the range of >2°C / s.
[0022] In the present invention, Ms refers to the martensitic transformation starting temperature.
[0023] The present invention obtains a complex phase structure composed of nano bainite + supercooled austenite by cooling the austenitized low alloy steel to a preset temperature at a first cooling rate. The first cooling rate to the preset temperature can avoid the formation of pearlite and ferrite structures, and avoid the upper bainite and granular bainite phase regions with coarse sizes, so as to obtain a nano-scale bainite structure; and then cools to room temperature at a second cooling rate to obtain a micro-nano structure of nano bainite + nano twin martensite + residual austenite. In the second cooling process, twin martensite with a nano spacing size can be partially generated to achieve ultra-high hardness performance, and obtain a low alloy ultra-high hardness steel with refined structure and excellent comprehensive mechanical properties.
[0024] Preferably, the insulation time is 30 to 100 minutes.
[0025] Preferably, the temperature of the tempering stabilization treatment is 180-300°C.
[0026] The beneficial technical effects of the present invention are as follows:
[0027] The present invention can obtain an ultrafine ultra-hard micro-nano structure composed of nano-scale bainite, nano-twin martensite, residual austenite and possible cementite multiphase by simply heat treating low-alloy steel under the condition of reducing the alloy element content and adjusting its process parameters. The ultrafine ultra-hard micro-nano structure significantly improves the hardness of the low-alloy steel. The present invention makes the matrix structure of the prepared low-alloy ultra-high hardness steel mainly ultrafine nano-bainite and nano-twin martensite lamellae through the design of alloy components and micro-nano structure, and the hardness can reach 63-68HRC.
[0028] The low-alloy ultra-high hardness steel alloy system of the present invention is reasonably controlled, the preparation process is simple and easy, it is conducive to industrial production, and the preparation efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the low alloy ultra-high hardness steel structure prepared in Example 1.
[0030] Figure 2 This is the TEM image of the low alloy ultra-high hardness steel structure prepared in Example 2.
[0031] Figure 3 This is the TEM image of the low alloy ultra-high hardness steel structure prepared in Example 3. DETAILED DESCRIPTION
[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] Example 1
[0037] Preparation of low alloy ultra-high hardness steel:
[0038] The main chemical components of low alloy steel are as follows: C 0.85%, Si 1.35%, Al 0.10%, Mo0.10%, Cr 1.20% and Fe balance; δ = 0.20; Ms = 220 °C;
[0039] Processing steps:
[0040] (1) Austenitization: The low alloy steel is austenitized at 860°C for 30 min.
[0041] (2) first stage cooling rate control: cooling the low alloy steel after austenitization treatment in step (1) to a first preset temperature of 240° C. at a first cooling rate of 15° C. / s, and keeping the temperature for 60 min;
[0042] (3) Second stage cooling rate control: cooling the low alloy steel after the first stage cooling in step (2) at a second cooling rate of 10° C. / s to a second preset temperature of 25° C.;
[0043] (4) Low temperature tempering: The low alloy steel after the second stage cooling in step (3) is kept at 200°C for 1 hour to stabilize the microstructure of the low alloy steel and obtain a low alloy ultra-high hardness steel.
[0044] The scanning electron microscope (SEM) image of the low alloy ultra-high hardness steel structure prepared in Example 1 is shown in Figure 1 .
[0045] from Figure 1 It can be seen that the microstructure of low alloy ultra-high hardness steel is bainite, martensite, retained austenite and cementite, with contents of 62%, 13.5%, 18% and 6.5% respectively. Among them, the thickness of bainite ferrite lath is 62.5nm, and the thickness of twin martensite lamella is 8.4nm.
[0046] The hardness of the low alloy ultra-high hardness steel prepared in Example 1 was measured to be 65.2HRC.
[0047] Example 2
[0048] Preparation of low alloy ultra-high hardness steel:
[0049] The main chemical components of low alloy steel are as follows: C 0.97%, Si 1.78%, Al 0.50%, Mo0.60%, Cr 1.75% and Fe balance; δ = 0.33; Ms = 200 °C;
[0050] Processing steps:
[0051] (1) Austenitization: The low alloy steel is austenitized at 880°C for 30 min.
[0052] (2) first stage cooling rate control: cooling the low alloy steel after austenitization treatment in step (1) to a first preset temperature of 190° C. at a first cooling rate of 25° C. / s, and keeping the temperature for 30 min;
[0053] (3) Second stage cooling rate control: The low alloy steel after the first stage cooling in step (2) is cooled at a second cooling rate of 15°C / s to a second preset temperature of 25°C.
[0054] (4) Low temperature tempering: The low alloy steel after the second stage cooling in step (3) is kept at 260°C for 1 hour to stabilize the microstructure of the low alloy steel and obtain a low alloy ultra-high hardness steel.
[0055] The transmission electron microscope (TEM) image of the low alloy ultra-high hardness steel structure prepared in Example 2 is shown in Figure 2 .
[0056] from Figure 2It can be seen that the microstructure of low alloy ultra-high hardness steel is bainite, martensite, retained austenite and cementite, with contents of 22%, 52.2%, 16% and 9.8% respectively. Among them, the thickness of bainite ferrite lath is 34.8nm, and the thickness of twin martensite lamella is 6.7nm.
[0057] The hardness of the low alloy ultra-high hardness steel prepared in Example 2 was measured to be 68.0 HRC.
[0058] Example 3
[0059] Preparation of low alloy ultra-high hardness steel:
[0060] The main chemical components of low alloy steel are as follows: C 0.82%, Si 1.62%, Al 0.36%, Mo0.40%, Cr 1.54% and Fe balance; δ = 0.24; Ms = 230 °C;
[0061] Processing steps:
[0062] (1) Austenitization: The low alloy steel was austenitized at 890°C for 30 min.
[0063] (2) first stage cooling rate control: cooling the low alloy steel after austenitization treatment in step (1) to a first preset temperature of 270° C. at a first cooling rate of 30° C. / s, and keeping the temperature for 100 min;
[0064] (3) Second stage cooling rate control: cooling the low alloy steel after the first stage cooling in step (2) at a second cooling rate of 20° C. / s to a second preset temperature of 25° C.;
[0065] (4) Low temperature tempering: The low alloy steel after the second stage cooling in step (3) is kept at 240°C for 1 hour to stabilize the microstructure of the low alloy steel and obtain a low alloy ultra-high hardness steel.
[0066] The transmission electron microscope (TEM) image of the low alloy ultra-high hardness steel structure prepared in Example 3 is shown in Figure 3 .
[0067] from Figure 3 It can be seen that the microstructure of low alloy ultra-high hardness steel is bainite, martensite and residual austenite, with contents of 70%, 12% and 18% respectively. Among them, the thickness of bainite ferrite lath is 112.2nm, and the thickness of twin martensite lamella is 14.7nm.
[0068] The hardness of the low alloy ultra-high hardness steel prepared in Example 3 was measured to be 63.2HRC.
[0069] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A low alloy ultra-high hardness steel, characterized in that: The raw material of the low alloy ultra-high hardness steel is low alloy steel; the matrix structure of the low alloy ultra-high hardness steel consists of nano-scale bainite, nano-twinned martensite lamellae and residual austenite, or consists of nano-scale bainite, nano-twinned martensite lamellae, residual austenite and cementite; The chemical composition of the low alloy steel, in addition to iron, includes, by mass percentage, 0.8% to 1.0% C, 1.2% to 1.8% Si, 0.05% to 0.5% Al, 1.0% to 1.8% Cr, 0% to 0.6% Mo and unavoidable impurities, wherein the mass percentage ratio of C, Si, Al, Cr and Mo meets the following conditions: 0≤δ≤0.83, δ=[Cr 1 / 3 -(Si-C)]×[(0.25×Mo+Al)] 1 / 2 .
2. The low alloy ultra-high hardness steel according to claim 1, characterized in that: The lath size of bainitic ferrite in the nano-scale bainite is 30-120 nm; the thickness of the nano-twinned martensite lamellae is 5-15 nm.
3. The low alloy ultra-high hardness steel according to claim 1, characterized in that: The content of the nano-scale bainite is 20-70%, the content of the residual austenite is 15-20%, and the content of the cementite is 0-10%.
4. The low alloy ultra-high hardness steel according to claim 1, characterized in that: The hardness of the low alloy ultra-high hardness steel is 63-68HRC.
5. A method for preparing low alloy ultra-high hardness steel according to any one of claims 1 to 4, characterized in that: The following steps are involved: The low alloy steel is subjected to austenitization treatment, then cooled to Ms-10 to Ms+50°C at a first cooling rate, kept warm, then cooled to 25±2°C at a second cooling rate, and finally subjected to tempering stabilization treatment to obtain a low alloy ultra-high hardness steel; The range of the first cooling rate is >5°C / s; The second cooling rate is in the range of >2°C / s.
6. The method for preparing low alloy ultra-high hardness steel according to claim 5, characterized in that: The insulation time is 30 to 100 minutes.
7. The method for preparing low alloy ultra-high hardness steel according to claim 5, characterized in that: The temperature of the tempering stabilization treatment is 180-300°C.
Citation Information
Patent Citations
Ultrahigh-hardness ultrahigh-strength special steel and production method thereof
CN107460405A
High-hardness ultra-high wear resistance steel plate and production method thereof
CN109023100A
A 700HBW grade ultra-high hardness protective steel plate and its manufacturing method
CN111485181B